2018
DOI: 10.1021/jacs.7b09573
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Desymmetrization of Methylenedianilines via Enzyme-Catalyzed Remote Halogenation

Abstract: Extensive effort has been devoted to engineering flavin-dependent halogenases (FDHs) with improved stability, expanded substrate scope, and altered regioselectivity. Here we show that variants of rebeccamycin halogenase (RebH) catalyze enantioselective desymmetrization of methylenedianilines via halogenation of these substrates distal to their pro-stereogenic center. Structure-guided engineering was used to increase the conversion and selectivity of these reactions, and the synthetic utility of the halogenated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 37 publications
0
65
0
3
Order By: Relevance
“…[45,54] Recently, desymmetrization of prochiral methylene dianilines by a RebH mutant was demonstrated by Lewis et al, providing an example of engineering the enantioselectivity of a flavin-dependent halogenase. [56] In our study, alteration of one residue within the active site allows for a tremendous influence on l-/d-selectivity and we were able to alter specificity of the substrate enantiomer. This points to an unexpected crucial role of Ser in substrate recognition presumably attractive for engineering of halogenase specificity.…”
Section: The Active-site Ser Residue Plays a Crucial Role In Enantiommentioning
confidence: 71%
“…[45,54] Recently, desymmetrization of prochiral methylene dianilines by a RebH mutant was demonstrated by Lewis et al, providing an example of engineering the enantioselectivity of a flavin-dependent halogenase. [56] In our study, alteration of one residue within the active site allows for a tremendous influence on l-/d-selectivity and we were able to alter specificity of the substrate enantiomer. This points to an unexpected crucial role of Ser in substrate recognition presumably attractive for engineering of halogenase specificity.…”
Section: The Active-site Ser Residue Plays a Crucial Role In Enantiommentioning
confidence: 71%
“…A phylogenetic tree of all characterized α‐KG‐dependent oxygenases and halogenases was generated and we could speculate that, using the AdeV sequence as a probe, we could find more halogenated nucleotide natural products through genome mining. The nucleoside halogenase may also aid us in creating new nucleoside analogues through biological, chemical, or biochemical routes for clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…Building on previous learnings, Payne et al recently reported the first enantioselective desymmetrization of methylenedianinelines catalyzed by engineered RebH variants. Docking simulations and structure guided mutagenesis afforded mutants with improved activity and altered selectivity [63]. Tailoring the substrate scope of enzymes towards desired molecules has also been approached through protein engineering.…”
Section: Substrate Scope and Regioselectivitymentioning
confidence: 99%